Evaluation of PAK Teachers' Competence and Professionalism in Improving the Quality of Students at Sihombu Public Elementary School 203 - Henri RH Hasugian (Jurnal Scientia, 2025)
This study aims to evaluate the competence and professionalism of Christian Religious Education (CRE) teachers at SD Negeri 203 Sihombu and their contribution to improving student quality. The study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, and documentation, while data analysis follows the Miles and Huberman model. The results show that the competence of CAR teachers, which includes pedagogical, professional, social, and personality aspects, has a significant effect on students' understanding of the material, motivation to learn, and application of moral values. Observations show that teachers with high competence are able to create effective learning, while teachers with low competence need to develop their methods. Students' perceptions confirm the success of teachers in instilling moral values, although there is still room for improvement in the use of learning media. Teacher documentation was mostly complete and met standards, indicating readiness in learning planning and evaluation. Data validity was ensured through triangulation and member checks. The research findings emphasize the importance of regular training, media innovation, and periodic monitoring as strategies for improving teacher competency, so that the quality of PAK learning can be optimized in shaping students who are faithful, have good character, and are of high quality.